2018
DOI: 10.1080/15476286.2018.1462652
|View full text |Cite
|
Sign up to set email alerts
|

The deterministic role of 5-mers in microRNA-gene targeting

Abstract: MiRNAs play a central role in physiological and pathological processes. Both for the biological understanding and for their clinical application, it is essential to understand the interaction of miRNAs and their targets. Target identification largely hinges on in-silico prediction, which requires a complete consideration of miRNA binding sites within the UTRs of target genes. Here, we show that 5-mer sites might also play an essential role for human miRNA-target binding. We implemented and employed an algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 66 publications
1
11
1
Order By: Relevance
“…Therefore, together with our data herein, multiple genes in the autophagy pathway have been shown to be regulated by miRNAs, including targeting of ATG2B by miR-130 in chronic lymphocytic leukemia [ 45 ] and ATG14 by miR-140 in multiple myeloma [ 46 ]. On the other hand, in contrast to previously reported that miRNA targeting was mediated through the putative SRBS of ≥ 6-mer [ 47 ], our data showed that additional two 5-mer binding sites in the 3’UTR of MAP1LC3B contributed to targeting by miR-342-3p, and hence similarly suggesting a role of 5-mer binding sites in miRNAs-mediated posttranscriptional regulation of target genes [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, together with our data herein, multiple genes in the autophagy pathway have been shown to be regulated by miRNAs, including targeting of ATG2B by miR-130 in chronic lymphocytic leukemia [ 45 ] and ATG14 by miR-140 in multiple myeloma [ 46 ]. On the other hand, in contrast to previously reported that miRNA targeting was mediated through the putative SRBS of ≥ 6-mer [ 47 ], our data showed that additional two 5-mer binding sites in the 3’UTR of MAP1LC3B contributed to targeting by miR-342-3p, and hence similarly suggesting a role of 5-mer binding sites in miRNAs-mediated posttranscriptional regulation of target genes [ 48 ].…”
Section: Discussioncontrasting
confidence: 99%
“…While miRNA gene targeting relies on a complementary binding of the seed region to the target gene, non-canonical binding between gene and miRNA also seems to have a deterministic influence on the targeting process ( 11 , 12 ). The limited understanding of the true complexity of the interactions between miRNAs and genes poses substantial challenges for the computational prediction of miRNA targets.…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental validations are necessary, they often significantly exceed the scope of scientific publications, even for one single miRNA. On the other hand, purely bioinformatical interaction studies lack predictive power, particularly for non-canonical miRNA targeting, with high false positive and false negative rates (Hart et al, 2018). Bioinformatically supported high-throughput techniques such as short RNA sequencing can serve as an integrative middle ground.…”
Section: Discussionmentioning
confidence: 99%